2020
DOI: 10.1186/s12879-020-4826-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine may reduce risk of Pneumocystis pneumonia in lupus patients: a Nationwide, population-based case-control study

Abstract: Background: Pneumocystis pneumonia (PCP) is increasingly being diagnosed in patients with systemic lupus erythematosus (SLE), and hydroxychloroquine (HCQ) has been found to possess antifungal activities. We hence aimed to investigate the association between HCQ and PCP risk among patients with SLE. Methods: Using the 1997-2013 nationwide claim data, we identified 24,343 newly-diagnosed SLE patients. We then identified 58 PCP cases and selected 348 non-PCP controls matching (1:6) by age, sex, disease duration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
19
2
Order By: Relevance
“…None of these patients were put on prophylaxis and all had LN, lymphopenia and low CD4+ T cell counts. Another registry study from Taiwan 63 reported an incidence of PJP of 0.24%, with higher risk in patients with severe LN (OR 6.7), those receiving higher doses of prednisone (5‐10 mg/d, OR 25.9; >10 mg/d, OR 287; compared to <5 mg/d), higher 3‐month cumulative dose of cyclophosphamide (≤1.4 g, OR 0.64; >1.4 g, OR 11.5; compared to no use) and use of MMF (OR 50.8). However, the 3‐month cumulative dose of hydroxychloroquine (HCQ) was associated with a reduced risk of pancytopenia (>14 g, OR 0.20; compared to no use).…”
Section: Resultsmentioning
confidence: 99%
“…None of these patients were put on prophylaxis and all had LN, lymphopenia and low CD4+ T cell counts. Another registry study from Taiwan 63 reported an incidence of PJP of 0.24%, with higher risk in patients with severe LN (OR 6.7), those receiving higher doses of prednisone (5‐10 mg/d, OR 25.9; >10 mg/d, OR 287; compared to <5 mg/d), higher 3‐month cumulative dose of cyclophosphamide (≤1.4 g, OR 0.64; >1.4 g, OR 11.5; compared to no use) and use of MMF (OR 50.8). However, the 3‐month cumulative dose of hydroxychloroquine (HCQ) was associated with a reduced risk of pancytopenia (>14 g, OR 0.20; compared to no use).…”
Section: Resultsmentioning
confidence: 99%
“…These drugs are believed to be relatively safe when administered within the clinically advised limits with mild side effects. Furthermore, Chloroquine derivatives have been tested on Pneumocystis pneumonia (PcP) for their therapeutic activity to repurposing antimalarial drugs for Pneumonia (Gomes et al, 2018;Yeo et al, 2020). Pneumonia is a lifethreatening symptom for advanced stage coronavirus infected patients and clinicians are using Chloroquine and its derivative Hydroxychloroquine to treat the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The risk for CMV viraemia is similar to that seen with azathioprine but the likelihood of tissue-invasive CMV disease is greater. 25 Neither sulfasalazine nor hydroxychloroquine are immunosuppressive, they do not appear to increase infection risk in rheumatic disease patients, and they may be protective against certain infections 27,28 and in the case of hydroxychloroquine against COVID-19 itself. 29 The latter is the subject of several ongoing clinical trials including the RECOVERY trial.…”
Section: Conventional Disease Modifying Anti-rheumatic Drugs (Dmards)mentioning
confidence: 99%